EFL Students’ Engagement in The Use of Digital Storytelling in Speaking Classroom - Rahmani, Kalisha Arlinda; Miftakh, Fauzi; Ridwan, Iwan (Jurnal Ilmiah Wahana Pendidikan, 2023)
English speaking skill is one of the important skills that must be possessed by students. Without having speaking skill, students cannot communicate properly. Indonesian students have been learning English since they were in elementary school to university. However, the fact is that students often find difficulties in learning English, especially in their speaking skills. Therefore, the teacher as an educator should prepare interesting learning methods for students to help them solve their problems. This study describes the implementation of Digital Storytelling in the speaking classroom. This study aims to investigate students’ engagement in implementing Digital Storytelling in speaking classroom. The method used in this research is descriptive qualitative. Participants in this study were 37 junior high school students in Karawang. Collecting the data in this study using observation and interviews. The results of this study indicate that students are actively in learning process to speak using Digital Storytelling, students feel happy and excited during the learning process, and students are motivated to improve their speaking skills using Digital Storytelling, and the use of Digital Storytelling is effective for learning to speak English.